Studi Performansi Algoritma Perencanaan Jalur diantara PRM, RRT, RRT* dan Informed-RRT - Nelci Dessy Rumlaklak; Yelly Y Nabuasa; Tiwuk Widiastuti (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2019)
This paper will discuss a comparative performance review of several path planning algorithms. This study compares five well-known path planning algorithms, namely the Probabilistic Roadmap (PRM), Rapidly-exploring Random Tree (RRT), RRT* and Informed-RRT* algorithm. Testing is done through simulation based experiments using python. The test was conducted using several existing benchmark cases, namely narrow, maze, trap and clutter environment. The optimality criteria compared are path costs, computational time and the total number of nodes in the tree needed. The results of this study will provide information to readers about which algorithm is most suitable for use in user applications where there are several working parameters to be optimized. The findings have been summarized in the conclusion section. Keywords Â: Motion planning, PRM, RRT, RRT*, Informed-RRT*